Professional development of higher education teachers: exploring visions and practices of Portuguese Universities (Revista Lusófona de Educação, 2025)
The article focuses on the inventory and analysis of teacher professional development policies and practices promoted by Portuguese public universities. In a context calling for change and innovation in higher education to meet contemporary societal challenges, the aim is to understand the institutional vision on the subject under study. It also seeks to identify the objectives associated with the dominant initiatives and practices within the national university landscape. Based on a phenomenological/interpretive approach, qualitative techniques were used to systematically analyse the strategic plans and activity plans (2014-2023). We also studied the institutional websites and the documents related to the creation of the Centres of Excellence and Pedagogical Innovation (CEIP). The results reveal the absence of a professional development culture for teachers in pedagogical areas, with the prevalence of incipient, fragmented views, often associated with the idea of isolated, short-term training aimed at developing specific skills. This scenario could change with the creation of CEIPs.Keywords - higher education; teacher professional development; Portuguese universities; pedagogical innovation